Computerised evaluation of furnace fields - Rabey, Christopher Charles (Department of Electrical Engineering, 2016)
The concept of using a submerged arc furnace for the reduction of ore to semi-refined metal was introduced early in the nineteenth century, and although much research has been done on the operation of the furnace, its design and construction still remain more of an art than a science. The aim of this thesis is to investigate, by means of various models, some of the basic parameters and fields of the arc furnace in an attempt to increase the understanding of its operation.